Pengaruh Brand Awareness, Brand Image, dan Brand Trust terhadap Keputusan Pembelian KFC di Suncity Mall Sidoarjo - Dhita Putri Natasha; Misti Hariasih; Muhammad Yani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Technological developments and changes in people's lifestyles have affected daily food preferences, where branded fast food is increasingly in demand because it is considered practical, modern, and a symbol of social status. Consumers prefer fast food restaurants such as KFC, McDonald's, and Hoka-Hoka Bento because they offer quality, speed, and innovation in products and promotions. KFC is one of the fastfood restaurants that is very popular with consumers, as seen from the results of the Top Brand Award survey, KFC has managed to maintain the top position for three consecutive years, from 2021 to 2023. This research was conducted using quantitative methods and the population is people who are KFC consumers at Suncity Mall Sidoarjo and consumers aged 17 years and over. The sample determination was carried out using non-probability sampling technique through purposive sampling method so that a sample of 96 respondents was obtained. The types of data in this study include primary data and secondary data, with data collection techniques using questionnaires. Data analysis in this study was carried out using SPSS version 25 which includes validity test, reliability test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression test, T test, and coefficient of determination (R2) test. So that the results obtained state that Brand Awareness, Brand Image, and Brand Trust have an effect on KFC purchasing decisions at Suncity Mall Sidoarjo.